Barriers and facilitators of deploying health kiosk in Iran: A qualitative study - Mozhgan Letafatnejad; Mohammadreza Maleki; Parvin Ebrahimi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: It is less than a decade in Iran that integrated health kiosks have been limitedly provided to public by private sector. Considering the significant benefits of them, this study aimed to identify the barriers and facilitators for deploying kiosks in Iran's formal health system in three phases, "design and construct, implement, and use." MATERIALS AND METHODS: This was a qualitative study in Iran, and the data were collected through 20 semi-structured interviews with experts in 2019. Participants were selected by purposeful method with the most diversity in terms of background and work experience; the interview texts were coded in MAXQDA10 software and analyzed through framework analysis. Participants' viewpoint was used to verify the data and observers' review to confirm them. RESULTS: The barriers for designing and constructing kiosks were identified in the form of two main themes: the overall structure of the country and the structure of the health system; the obstacles for implementing were categorized in one main theme, lack of sources; and the barriers to use were also fall into four themes related to people, policymakers, service providers, and designers of kiosks. The facilitators at construction and implementation phases included the overall structure of the country and the structure of health system. At the use stage, the facilitators related to people, health and insurance policymakers, and owners and constructers were identified. CONCLUSION: It is possible to deploy health kiosks in the Iranian formal health system, although there are some time-consuming and costly barriers which can be overcome by the strengths and opportunities of the system.